Implementasi Audit Persedian pada UMKM Cireng Bontot Ibu Salminah Kota Serang Banten - Sari, Irna Maya; Khomilah, Shally (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The purpose of the MSME audit Cireng Bontot Ibu Salminah is an UMKM that produces a typical Serang dish called Cireng Bontot. This UMKM is capable of producing 800-1000 pieces of cireng per day, but during Ramadan and Eid al-Fitr, the demand increases significantly. However, this large production is not matched by significant business development because this UMKM does not implement business recording and accounting to support their business. This service is the second time for our team in carrying out the tridharma; during the first service, we created accounting record books, namely the inventory book, sales book, and cash receipt book. As a result, the UMKM has been able to maintain records quite well, leading to better financial management. For the sustainability of the development of UMKM Cireng Bontot Ibu Salminah, we continue this service activity with the theme of Inventory Audit Implementation. Where inventory is an important aspect of food production businesses that have a large stock of raw materials, it must be maintained to prevent fraud and loss that could disrupt business development